Enhancing Students' Critical Thinking in Organic Chemistry: A Quasi-Experimental Study on PBL-Based E-Modules - Helsy, Imelda; Rizkiyani , Sinta; Sari, Sari; Sunarya, Risa Rahmawati; Aisyah, Riri (Journal of The Indonesian Society of Integrated Chemistry, 2026)
Critical thinking skills are an essential 21st-century competency; however, students' mastery of protein concepts in Organic Chemistry remains low. This study, employing a quasi-experimental design (pretest-posttest nonequivalent control group) involving 77 undergraduate students, aimed to analyze the improvement in students' critical thinking skills through the implementation of an e-module-assisted Problem-Based Learning (PBL) model, as compared to conventional instruction. The research instrument consisted of a test designed to measure four critical thinking indicators: interpretation, analysis, inference, and evaluation. The results revealed that the experimental group achieved an average N-gain of 0.335 (moderate category), whereas the control group attained an average N-gain of only 0.07 (low category). However, the Mann-Whitney U test indicated no statistically significant difference in the improvement of critical thinking skills between the experimental and control groups (p = 0.324). Nevertheless, descriptive statistics demonstrated that the experimental group exhibited a higher average improvement in critical thinking skills than the control group. These findings suggest that the implementation of e-module-assisted PBL has the potential to foster students' critical thinking skills, despite the lack of a statistically significant difference when compared to conventional instruction